TRAUMA DAN RESILIENSI PADA WANITA PENYINTAS KEKERASAN DALAM RUMAH TANGGA - Sherly Deborah; Ayu Muthmainnah; Louis Herlinda; Suhiandy Sulaiman Tanawi (MANASA, 2018)
According to National Comission of Women in Indonesia, there are 259.150 cases about battered women which has reported and managed in the year of 2016, domestic violence as an action or behavior that have been done for specific purpose, thereby can harm other individuals, either physically and mentally. This act of domestic violence can be shown in vary behavior such as physical, sexual, emotional abuse, controlling another individual to obtain a lot of benefits. Everybody has their own resilience’s level and for victims of domestic violence as well.Resiliency or self-resiliency is a form of hardiness of individuals to encounter problems even in traumatic condition. From the traumatical problems, resiliency is about how individuals being able to start over life and being able to overcome all obstacles well. Domestic violence’s victims are expected to have high level of resilience in order to rearrange their life after the trauma caused by their significant other, enhance skills, and being functionally adaptive.